Integrating e-servqual and kano model to improve adorable projects website service quality - Fauziyah, Rahma; Rohayati, Yati; Sagita, Boby Hera (Jurnal Sistem dan Manajemen Industri, 2019)
This study aims to determine the classification of attribute needs of purchasing services through the Adorable Projects website by using the integration of e-Servqual and Kano Models. The selection of these objectives is based on the low level of website usage as an online purchasing tool owned by Adorable Projects. The classificatiÂon activity aims to make it easier for Adorable Projects to make improveÂments to the quality of its website services. Based on the results of data processing, 24 attributes in the must be the category, two attributes in the one-dimensional category, three attributes in the attractive category, and four attributes in the indifferent category. Strategy priority in developing service quality by increasing the diversity of service delivery features and product review features. The integration of e-Servqual and Kano can assist business owners in making strategic decisions related to improving the service quality.